Children's music of the Shangana-Tsonga - Johnston, Thomas F. (International Library of African Music, 1987)
Among the Shangana-Tsonga of the Northern Transvaal and Mozambique (hereafter referred to as the Tsonga), children's music occurs seasonally within a broad range of social contexts, the separate boundaries of which are not always sharply defined. They include winter fireside storytelling, where the audience of children is assigned a recurring stereotyped response, and where the song-within-the-story often possesses magical power which overcomes blocks encountered by the hero. They include children's games played before or after the rainy season when the ground is firm enough, and light subsistence activities where children traditionally help, as with herding the cattle.
Keywords: African Music